Terapi Relaksasi Otot Progresif sebagai Upaya dalam Menurunkan Ansietas pada Penyakit Fisik - Yefta Primasari; Endah Yuliany Rahmawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Anxiety is often experienced by many people in their daily life. According to data of WHO, there are about 35 million people affected by depression, 60 million people with bipolar disorder, 21 million affected by schizophrenia, and 47.5 million affected by dementia. Meanwhile in Indonesia, the prevalence of people with mental emotional disturbance with symptomps of depression and anxiety aged 15 years or over reaches 9.8% of the Indonesian population, and the prevalence of mental disorders reaches 7 per mil. One of the non-pharmacological therapies that can help to reduce anxiety is the Progressive Muscle Relaxation therapy. This study aims to determine the effect of Progressive Muscle Relaxation therapy on reducing anxiety. The method of writing this article uses Systematic review through article searching process on electronic databases (Science Direct, ProQuest, Scopus, and Google Scholar). This review uses keywords namely